The rhetoric of economics - McCloskey, Deirdre N. (Rhetoric of the human sciences., 1998)
A classic in its field, this pathbreaking book humanized the scientific rhetoric of economics to reveal its literary soul. In this completely revised second edition, Deirdre N. McCloskey demonstrates how economic discourse employs metaphor, authority, symmetry, and other rhetorical means of persuasion. The Rhetoric of Economics shows economists to be human persuaders, poets of the marketplace, even in their most technical and mathematical moods.